Development and controlling factors of shale lithofacies cycles in a continental rift basin: A case study of Es4u in the Boxing Subsag of Dongying Sag, Bohai Bay Basin, China - Fang, Zhengwei; Zhang, Liqiang; Ma, Cunfei (Frontiers in Earth Science, 2023)
The shale of the upper Es4 formation (Es4u), deposited during the Eocene in the Boxing Subsag of the Dongying Sag, is a typical set of lime-rich lacustrine shale in a continental rift basin. Through logging data interpretation, core and thin section observations, and geochemical elements [obtained by X radial fluorescence (XRF) mud logging] analysis, the development and controlling factors of lithofacies cycles of Es4u shale were analyzed. The results show that 22 types of lithofacies with typical characteristics are developed in Es4u, indicating the sedimentary environments, such as lower lakeshore (LL) slope zone; upper, middle, and lower shallow-lake slope zones; semi-deep-lake zone; and deep-lake zone. Lithofacies cycles in three scales are recognized in Es4u: small-scale lithofacies cycles indicated by alternate development of two lithofacies, mesoscale lithofacies cycles indicated by the repetition of lithofacies associations or regular variation of multiple lithofacies, and large-scale lithofacies cycles indicated by regular variation of well logging curves, which have the average thickness of approximately 0.4, 5, and 35 m, respectively. According to the vertical variation of astronomical parameters and lithofacies cycles, the periodic change in long eccentricity has a close relationship with the large-scale lithofacies cycle, the periodic change in slope is closely relative to the mesoscale lithofacies cycle, and the periodic change in precession is closely related to small-scale lithofacies cycle. However, the periodic change in short eccentricity correlates poorly with lithofacies cycles. The climate change reflected by long eccentricity and slope is quite distinct from the actual basin climate reflected by the paleoclimatic parameters (e.g., Rb/Sr and Sr/Cu), indicating that the basin paleoclimate was greatly influenced by the paleogeological conditions. For shale in Es4u of the Boxing Subsag, approximately 55% of the shale stratigraphic record is dominantly controlled by the astronomical climate and 45% by the paleogeological conditions. Affected by the paleogeological conditions, large-scale and mesoscale lithofacies cycles are different in lithofacies types and superimposition patterns, and just small-scale lithofacies cycles are found repetitive vertically. These findings suggest that the lithofacies cycles of shale in a continental rift basin are a product of astronomical driving mechanism (Milankovitch forcing) and variation of local paleogeological conditions, which is apparently different from the sedimentary record of marine shale that is evidently controlled by the Milankovitch cycle. Therefore, the lithofacies cycles should be comprehensively analyzed under the background of actual basin paleoclimate.